Landwirtschaftliche Nutzung von Moorflächen in Deutschland. Sozioökonomische Aspekte einer klimaschonenden Bewirtschaftung. - Schaller, Lena Luise (My University, 2015)
In der Arbeit werden landwirtschaftliche und gesellschaftliche Ausgangsbedingungen der Umsetzung klimaschonender Moorbewirtschaftung, deren ökonomische Konsequenzen für landwirtschaftliche Betriebe und die resultierenden Emissionsvermeidungskosten analysiert. Datengrundlage sind Betriebs- und Stakeholderbefragungen in sechs deutschen Moorgebieten. Die Ergebnisse zeigen, dass die Umsetzungspotenziale klimaschonender Moorbewirtschaftung stark von regionalen Ausgangsbedingungen geprägt sind und die Kosten der Umsetzung betriebsindividuell stark variieren.

The study analyses agricultural and societal prerequisites for the implementation of climate-friendly peatland management in Germany. Moreover it calculates related economic consequences for farmers and resulting emission abatement costs. The work is based on an extensive farm and stakeholder survey in six German peatland areas. Results show that the potential of climate-friendly peatland management is strongly determined by regional conditions and that the implementation costs and abatement costs strongly vary among individual farms.
Agricultural use of peatlands in Germany. Socio-economic aspects of climate-friendly management.
Keywords: Landwirtschaft; Moor; Bewirtschaftung; Landwirtschaftliche Bodennutzung; Klima; Landwirtschaftlicher Betrieb; Flächennutzung; Befragung; Empirische Untersuchung; Moorschutz; Klimaschutz